Data Encryption and IAM Policies: Best Practices for AWS Ecosystems (Cybersecurity and Network Defense Research, 2022)
Securing sensitive data in AWS ecosystem remains a critical concern for enterprises as cloud adoption increases. The aim of this paper is to explore the best practises for data encryption Identity and Access Management (IAM) policies in AWS To ensure robust security postures against new evolving threats. As we provide an in-depth analysis of AWS-native encryption mechanism which includes AWS Key Management Service (KMS), envelope encryption, and hardware security modules (HSMs), and also examines the effectiveness in securing data confidentiality and integrity.